A Functional CT Contrast Agent for In Vivo Imaging of Tumor Hypoxia. Issue 29 (27th June 2016) - Shi, Hongyuan; Wang, Zhiming; Huang, Chusen; Gu, Xiaoli; Jia, Ti; Zhang, Amin; Wu, Zhiyuan; Zhu, Lan; Luo, Xianfu; Zhao, Xuesong; Jia, Nengqin; Miao, Fei
Abstract : Hypoxia, which has been well established as a key feature of the tumor microenvironment, significantly influences tumor behavior and treatment response. Therefore, imaging for tumor hypoxia in vivo is warranted. Although some imaging modalities for detecting tumor hypoxia have been developed, such as magnetic resonance imaging, positron emission tomography, and optical imaging, these technologies still have their own specific limitations. As computed tomography (CT) is one of the most useful imaging tools in terms of availability, efficiency, and convenience, the feasibility of using a hypoxia‐sensitive nanoprobe (Au@BSA‐NHA) for CT imaging of tumor hypoxia is investigated, with emphasis on identifying different levels of hypoxia in two xenografts. The nanoprobe is composed of Au nanoparticles and nitroimidazole moiety which can be electively reduced by nitroreductase under hypoxic condition. In vitro, Au@BSA‐NHA attain the higher cellular uptake under hypoxic condition. Attractively, after in vivo administration, Au@BSA‐NHA can not only monitor the tumor hypoxic environment with CT enhancement but also detect the hypoxic status by the degree of enhancement in two xenograft tumors with different hypoxic levels. The results demonstrate that Au@BSA‐NHA may potentially be used as a sensitive CT imaging agent for detecting tumor hypoxia. Abstract : A Au@BSA‐NHA nanoprobe is developed as a hypoxia‐sensitive computed tomography (CT) contrast agent for imaging hypoxic status of tumors in vivo. After intravenous injection, the nanoprobe shows different CT enhancement degree in two xenograft models with different hypoxic levels, which enables Au@BSA‐NHA to be used as an imaging agent to reflect different tumor hypoxic status in vivo.